Natural Compound Library Screening Identifies Oroxin A for the Treatment of Myocardial Ischemia/Reperfusion Injury - Cheng, Xingdong; Huang, Tingting; Wang, Chunhui; Hao, Shuang; Shu, Liliang; Wang, Shixiong; Cheng, Gao; Zhang, Qiaoyun; Huang, Jian; Chen, Chen (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion injury (MI/RI) is a serious pathophysiological process relating to cardiovascular disease. Oroxin A (OA) is a natural flavonoid glycoside with various biological activities. However, its effect on the pathophysiological process of MI/RI has not yet been reported. The aim of this study was to determine whether OA could alleviate MI/RI induced inflammation and pyroptosis in vivo and in vitro, providing a novel therapeutic regimen for the treatment of MI/RI. A high-throughput drug screening strategy was employed to test 2,661 natural compound libraries that can alleviate MI/RI in vivo and in vitro. The rat model of MI/RI was established by ligating the left anterior descending (LAD) coronary artery. H9c2 cells were subjected to oxygen-glucose deprivation/reperfusion (OGD/R) to simulate MI/RI. The results show that OA is able to significantly inhibit apoptosis, pyroptosis and the inflammation response (TNF-α, IL-6, IL-8, IL-10, IL-1β, IL-18) in vivo and in vitro, and reduce the release of myocardial enzymes (cTnI, cTnT, CK-MB, LDH, AST). In the rat MI/RI model, OA can not only improve cardiac function and reduce inflammatory cell infiltration but also reduce myocardial infarct size. The results revealed that OA is an effective remedy against MI/RI as it reduces the inflammatory response and inhibits pyroptosis. This may provide a new therapeutic target for the clinical treatment of MI/RI.